Türk Borçlar Kanunu M. 350-351 Çerçevesinde “Gerçek” İhtiyaç Kavramı Üzerine Düşünceler - Çelik, Nazlı Hilal (Legal Yayıncılık, 2021)
Kiraya verenden kaynaklanan tahliye sebepleri Türk Borçlar Kanunu’nun 350 ve 351’inci maddelerinde düzenlenmiştir. Aynı sebepler İsviçre hukukunda Art. 261 Abs. 2a, 271a Abs. 3a ve 272 Abs. 2d OR’da düzenlenmiştir. Bu çalışmada öncelikle kiraya veren ve yeni malik kavramlarına dahil olan kişiler belirlenmiş, sonrasında ise gerçek ihtiyacın niteliği değerlendirilmiştir. Gerçek bir ihtiyaçtan kasıt samimi, güncel ve ciddi nitelikteki ihtiyaçlardır. Bu hususların her bir olay ve kişi için ayrı değerlendirilmesi gerekir.

The reasons for evacuation arising from the leaser are regulated in the articles 350 and 351 of the Turkish Code of Obligations. The same reasons are regulated in Swiss law Art. 261 Abs. 2a, 271 a Abs. 3a, and 272 Abs. 2d OR. In this study, first of all, the people who are included in the concepts of leaser and the new owner were determined and then the nature of the real need was evaluated. What is meant by a real need is sincere, up-to-date, and serious needs. These issues should be evaluated separately for each case and person.
Thoughts on the Concept of "Real" Needs In the Framework of the Turkish Code of Obligations, Article 350-351
Keywords: Kira Sözleşmesi; Gerçek İhtiyaç; Kiraya Veren; Malik; Contract of Hire; Real Needs; Lessor; Owner